Ventriculoperitoneal shunt is associated with increased cerebrospinal fluid protein level in HIV-infected cryptococcal meningitis patients - Tao, Ran; Xu, Lijun; Guo, Yongzheng; Xu, Xiaoke; Zheng, Jiesheng; Zhu, Biao (BMC infectious diseases, 2022)
Background The impact of ventriculoperitoneal shunt on cerebrospinal fluid (CSF) biochemical profiles in HIV-associated cryptococcal meningitis (HCM) patients remains unclear. Methods Twenty-nine HCM patients who underwent ventriculoperitoneal shunt (the VPS group) and 57 HCM patients who did not undergo ventriculoperitoneal shunt (the non-VPS group) were enrolled in this propensity score matching analysis. Demographic characteristics, symptoms, CSF biochemical profiles, and adverse events were compared between the two groups. The Kaplan–Meier method was used to analyze the survival rate. Univariate and multivariate logistic regression analyses were performed to identify the risk factors for increased CSF protein levels. Results After 24 weeks of treatment, the intracranial pressure was significantly lower in the VPS group than in the non-VPS group (mmH 2 O; 155.0 [120.0–190.0] vs. 200.0 [142.5–290.0]; P = 0.025), and the rate of neuroimaging improvement was significantly higher in the VPS group (16/17 [94.1%] vs. 2/10 [20%]; P < 0.001). Furthermore, the 24-week cumulative survival rates were also significantly higher in the VPS group (96.6% vs. 83.5%, P = 0.025). Notably, the CSF protein levels were higher in the VPS group than in the non-VPS group at each examination time, and the CSF glucose was lower in the VPS group than in the non-VPS group even at the 12-week follow-up. In the multivariate analysis, we found that VPS placement was an independent risk factor for increased CSF protein (odds ratio [OR]: 27.8, 95% confidence interval [95% CI] 2.2–348.7; P = 0.010). Conclusions VPS decreased the intracranial pressure, improved neuroimaging radiology and reduced the 24-week mortality in HCM patients. However, VPS significantly altered the CSF profiles, which could lead to misdiagnosis of tuberculous meningitis and some of them were diagnosed with immune reconstitution inflammatory syndrome. Physicians should be aware of these changes in the CSF profiles of patients with HCM undergoing VPS.